Three-Dimensional Printing Model as a Tool to Assist in Surgery for Large Mandibular Tumour: a Case Report - Kazuyuki Yusa; Hideyuki Yamanochi; Akira Takagi; Mitsuyoshi Iino (Stilus Optimus, 2017)
Objectives: Recently, three-dimensional printing models based on preoperative computed tomography and magnetic resonance imaging images have been widely used in medical fields. This study presents an effective use of the three-dimensional printing model in exploring complex spatial relationship between the tumour and surrounding tissue and in simulation surgery based planning of the operative procedure. Material and Methods: The patient was a 7-year-old boy with ameloblastic fibro-odontoma. Prior to surgery, a hybrid three-dimensional printing model consisting of the jaw bone, the tumour and the inferior alveolar nerve was fabricated. After the simulation surgery based on this model, enucleation of the tumour, leaving tooth 46 intact (Universal Numbering System by ADA) safe, was planned. Results: Enucleation of the tumour was successfully carried out. One year later, healing was found to be satisfactory both clinically and radiographically. Conclusions: The study presented an effective application of a novel hybrid three-dimensional printing model composed of hard and soft tissues. Such innovations can bring significant benefits, especially to the field of oncological surgery.